2020
DOI: 10.1161/jaha.120.017020
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Carotid Intima‐Media Thickness and Plaque Heterogeneity With the Risks of Stroke Subtypes and Coronary Artery Disease in the Japanese General Population: The Circulatory Risk in Communities Study

Abstract: Background Evidence on the associations of carotid intima‐media thickness and carotid plaque characteristics with stroke subtypes and coronary artery disease risks in Asians is limited. This study investigated these associations in the Japanese general population. Methods and Results Maximum intima‐media thicknesses of both the common carotid artery and internal carotid artery and carotid plaque characteristics were evaluated in 2943 Japanese subjects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Carotid plaque is considered a surrogate marker of subclinical atherosclerosis and is associated with the risk of stroke, MI, and mortality ( 2 , 3 , 20 ). In the present results, we found that carotid artery plaque significantly increased the risk of all-cause mortality by 1.73 times in the general Chinese population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carotid plaque is considered a surrogate marker of subclinical atherosclerosis and is associated with the risk of stroke, MI, and mortality ( 2 , 3 , 20 ). In the present results, we found that carotid artery plaque significantly increased the risk of all-cause mortality by 1.73 times in the general Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Carotid artery plaque is a marker of degenerative changes and structural changes in atherosclerosis. The previous study shows that the presence of carotid plaque is associated with the risk of stroke, myocardial infarction (MI), and mortality ( 2 , 3 ). Meta-analysis shows that carotid plaque is also a better predictor of future cardiovascular events than the intima-media thickness ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have reported that lung function is inversely associated with cIMT [10][11][12][13][14][15][16][17][18] . However, studies demonstrating the association between lung function and cIMT among never smokers are limited 13,[15][16][17] .…”
Section: Advance Publication Journal Of Atherosclerosis and Thrombosismentioning
confidence: 97%
“…Previous studies have reported that lower lung function is related to an increased risk of coronary heart disease (CHD), stroke, and CVD [2][3][4][5][6] . Carotid intima-media thickness (cIMT) is widely used as a marker for atherosclerosis, and several studies have reported that a higher cIMT is related to the incidence of CHD, stroke, and CVD [7][8][9][10][11] . type 1 survey (40,433 participants) was conducted at specific municipal health check-up sites.…”
Section: Introductionmentioning
confidence: 99%
“…In the Circulatory Risk Communities Study, heterogeneous plaques correlated positively with increased risk of total stroke, ischemic stroke, lacunar infarction, coronary artery disease, and total cardiovascular disease. In addition, patients with markedly irregular or ulcerated plaques had a significantly higher risk for coronary artery disease and total cardiovascular disease but not stroke ( 28 ). Recording plaque location, thickness, area, and number is recommended for a more precise description of carotid plaques ( 31 ).…”
Section: Direct Parameters Of Carotid Ultrasonographymentioning
confidence: 99%